Relationships among gut microbiota, plasma metabolites, and juvenile idiopathic arthritis: a mediation Mendelian randomization study - Gao, Bingjun; Wang, Zhe; Wang, Kunyao; Lei, Yinghan; Zhuang, Yan; Zhou, Zhonghua; Chen, Junfei (Frontiers in Microbiology, 2024)
Objective The objective of this study is to investigate the causal relationship between gut microbiota and juvenile idiopathic arthritis, and to identify and quantify the potential role of plasma metabolites as mediators. Methods Using summary-level data from genome-wide association studies, a two-sample Mendelian randomization was conducted involving 131 gut microbiota genus, 1,400 plasma metabolites, and juvenile idiopathic arthritis. Additionally, a two-step approach was employed to quantify the proportion of the effect of gut microbiota on juvenile idiopathic arthritis mediated by plasma metabolites. Effect estimation primarily utilized Inverse Variance Weighting, with further validation using Bayesian weighted Mendelian randomization. Results In our MR analysis, a positive correlation was observed between Rikenellaceae and the risk of juvenile idiopathic arthritis, while Dorea showed a negative correlation with juvenile idiopathic arthritis risk. Mediation analysis indicated that Furaneol sulfate levels acted as a mediator between Dorea and juvenile idiopathic arthritis, with an indirect effect proportion of 19.94, 95% CI [8.86–31.03%]. Conclusion Our study confirms a causal relationship between specific microbial genus and juvenile idiopathic arthritis, and computes the proportion of the effect mediated by plasma metabolites, offering novel insights for clinical interventions in juvenile idiopathic arthritis.